High-cycle notch sensitivity of alloy steel ASTM A743 CA6NM used in hydrogenator turbine components - José Alexander Araújo; Jorge Luiz de Almeida Ferreira; Braitner Lobato da Silva (Fracture and Structural Integrity)
The presence of notches and other stress concentrations in turbine blades and other notch hydraulic components is a current problem in engineering. It causes a reduction of endurance limit of material. In that sense, specimens of the ASTM A743 CA6NM alloy steel using in several hydrogenator turbine components was tested. The specimens were tested under uniaxial fatigue loading with a load ratio equal to -1, and the considered stress concentration factors, Kt, values, calculated with respect to net area, were 1.55, 2.04 and 2.42. In order to determine the fatigue limit for such notch type, a reduction data method by Dixon and Mood, Staircase method was used. This approach is based on the assumed target distribution of the fatigue limit. For such geometry at least 8 specimens were tested. In addition, the Peterson and Neuber’s notch fatigue factor were compared through fatigue notch reduction factor, Kf, obtained from experimental data. According to results obtained it was possible to conclude that the tested material is less sensitive to notches than the prediction of the Peterson and Neuber’s empirical models.